Pengaruh Literasi Finansial, Inklusi Keuangan, Teman Sebaya, dan Kontrol Diri terhadap Perilaku Menabung Mahasiswa - Ericka Berliani Putri; Eko Wahjudi (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2022)
Savings can be said to be a savior when economic conditions are not good. In order to have sufficient savings, it is necessary to have good saving behavior. This study was conducted with the intention of knowing the effect of financial literacy, financial inclusion, peers, and self-control simultaneously and partially on the saving behavior of 2018 Accounting Education undergraduate students at the State University of Surabaya. This type of research is quantitative with data collection techniques using questionnaires. The data analysis technique used multiple linear regression. The results of this study are: (1) financial literacy, peers, and self-control each do not have an impact on student saving behavior, (2) financial inclusion partially has a positive impact on student saving behavior, and (3) financial literacy, financial inclusion, peers, and self-control together have an impact of 58.2% on student saving behavior.